2019
DOI: 10.1111/aos.14221
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of retinal layer thickness in acute anterior uveitis: an optical coherence tomography study

Abstract: Purpose: To determine the changes in peripapillary retinal nerve fiber layer (pRNFL), macular and ganglion cell-inner plexiform layer (GC-IPL) thicknesses in patients with acute anterior uveitis (AAU). Methods: Patients diagnosed with unilateral non-infectious AAU and normal control were enrolled retrospectively. Optical coherence tomography scans were performed during the initial active phase and inactive phase of AAU. Patients were followed for at least 3 months after resolution of inflammatory activity. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It was reported that the thickness of entire retina gets thickened with acute anterior uveitis, which implies the hyaluronic acid treatment reduced the degree of inflammation in retina while Solcoseryl treatment did not affect on retinal inflammation. 21 When the thickness of each layer was compared, the thickness of GCL and ILM was increased in all treatment groups compared to the control, with significant difference in Solcoseryl gel treatment group (p < 0.05). Also, IPL thickness was increased in all treatment groups, with significant difference in hyaluronic acid and Solcoseryl gel treatment groups (p < 0.01).…”
Section: Discussionmentioning
confidence: 86%
“…It was reported that the thickness of entire retina gets thickened with acute anterior uveitis, which implies the hyaluronic acid treatment reduced the degree of inflammation in retina while Solcoseryl treatment did not affect on retinal inflammation. 21 When the thickness of each layer was compared, the thickness of GCL and ILM was increased in all treatment groups compared to the control, with significant difference in Solcoseryl gel treatment group (p < 0.05). Also, IPL thickness was increased in all treatment groups, with significant difference in hyaluronic acid and Solcoseryl gel treatment groups (p < 0.01).…”
Section: Discussionmentioning
confidence: 86%
“…Inflammatory mediators have been reported to be associated with macular edema in uveitis. [17][18][19][20][21] Herein, we demonstrated a moderate positive linear relationship between macular thickening and optic disc swelling, particularly in eyes with ODH on FA. It can be assumed from these findings that the same inflammatory mechanism affects both the macula and optic disc.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, peripapillary RNFL thickness was also known to be affected by many types of uveitis. 7,8,16,17 Lee et al 18 reported a significant thickening on the RNFL as well as the macular in patient with active anterior uveitis and suggested that peripapillary RNFL thickness may be useful in assessing disease activity. Our study results coincide with previous studies to some degree, although they did not consider the relationship between OCT and angiographic findings.…”
Section: Discussionmentioning
confidence: 99%
“…The substructure of retinal/choroidal lesions can be assessed by OCT and frequently reveals hyperreflective aspects [40, 43, 90]. Furthermore, dependent on disease entity and activity, specific retinal layers can be disrupted/thickened/altered in characteristic ways [43, 91, 92]. For example, disruption of the ellipsoid zone in multiple evanescent white dot syndrome (MEWDS) is thought to correspond to swollen photoreceptor bodies [43].…”
Section: Methodsmentioning
confidence: 99%